PERAN KEBIJAKAN FISKAL DAN MONETER DALAM PEREKONOMIAN INDONESIA DARI HAMBATAN DAN UPAYA PENANGGULANGANNYA - Kartika, Rika (Yayasan Education and Social Center, 2024)
This research examines the facts about the implementation of Indonesia's fiscal and monetary policies and the obstacles. This literature research aims to compile and describe policy enforcement. The research was carried out using the type of library research. In this research, we use a qualitative approach which aims to examine existing social phenomena in more depth. This research uses reference books and journal articles related to the discussion in this journal. The Government & Bank Indonesia work together in creating fiscal and monetary policies that influence inflation, financial stability, or increase economic growth. State income or expenditure regulated in the APBN Law, and tax regulations to increase state revenues are part of the fiscal policy running in Indonesia. On the other hand, the Indonesian Central Bank implements monetary policy in Indonesia against the background of low interest rates and stable rupiah exchange rates. However, there are several limitations to the effective implementation of Indonesia's fiscal and monetary policies, and inequality in the MSME sector remains limited, which hinders its role in enhancing economic growth and providing job vacancies. and the lack of public education and financial literacy which hampers the transmission of Bank Indonesia's monetary policy to the real sector